(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Access to financial services is widely recognized as a vital catalyst for global economic development and poverty reduction. In this era of digital transformation, the concept of financial inclusion has undergone various changes, with digital technologies assuming a pivotal role in extending financial services to historically underserved communities. This systematic literature review conducts a comprehensive analysis of the existing corpus of research dedicated to digital financial inclusion, shedding light on prominent trends, knowledge gaps, and emerging themes in the field. Employing the PRISMA review methodology, we executed a systematic literature review (SLR) with a specific focus on digital financial inclusion. This SLR successfully identified and examined 30 relevant studies spanning the period from 2015 to 2022, sourced from reputable databases such as Scopus. The findings derived from this review underscore that a substantial portion of the selected studies sought to establish a foundational understanding related to digital financial inclusion. Moreover, the insights generated by this research offer valuable guidance to scholars interested in delving deeper into the realm of digital financial inclusion.